Enhancing MSME Competitiveness Through Financial Literacy and Digital Transformation in Indonesia - Idrus, Muhammad Ishlah; Rastina (Economics and Business Journal (ECBIS), 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a cornerstone of Indonesia's economy, contributing 60.5% to the national GDP and employing 97% of the workforce. However, MSMEs face challenges such as low financial literacy and limited adoption of digital technologies, which hinder their competitiveness in the global market. This study explores the synergistic role of financial literacy and digital transformation in enhancing MSME performance and competitiveness. Using a qualitative approach, data were collected through in-depth interviews, focus group discussions, and policy document analysis. The findings reveal that the average financial literacy level among MSME actors in Indonesia is only 38%, leading to poor financial management and limited access to formal financing. On the other hand, only 16% of MSMEs have integrated digital technologies into their operations, with those who did reporting significant improvements in efficiency and revenue. The integration of financial literacy with digital tools was found to have a multiplier effect, enabling better resource management, improved decision-making, and enhanced market competitiveness. This study highlights the importance of targeted policies to combine financial literacy training with digital technology adoption. By addressing challenges such as infrastructure limitations and resistance to change, stakeholders can foster inclusive economic growth and empower MSMEs to thrive in the digital economy.